Checked patterned elemental distribution in AlGaAs nanowire branches via vapor–liquid–solid growth. Issue 29 (16th July 2020) - Boras, Giorgos; Yu, Xuezhe; Fonseka, H. Aruni; Zhang, Dong; Zeng, Haotian; Sanchez, Ana M.; Liu, Huiyun
Abstract : Ga-rich stripes parallel to the growth direction of AlGaAs nanowire branches intersect with a periodic arrangement of Ga-rich stripes perpendicular to them, leading to the realization of a checked pattern of compositional distribution. Abstract : Morphology, crystal defects and crystal phase can significantly affect the elemental distribution of ternary nanowires (NWs). Here, we report the synergic impact of the structure and crystal phase on the composition of branched self-catalyzed Al x Ga1− x As NWs. Branching events were confirmed to increase with Al incorporation rising, while twinning and polytypism were observed to extend from the trunk to the branches, confirming the epitaxial nature of the latter. The growth mechanism of these structures has been ascribed to Ga accumulation at the concave sites on the rough shell. This is in agreement with the ab initio calculations which reveal Ga atoms tend to segregate at the trunk/branch interface. Notably, uncommon, intricate compositional variations are exposed in these branched NWs, where Ga-rich stripes parallel to the growth direction of the branches intersect with another set of periodic arrangements of Ga-rich stripes which are perpendicular to them, leading to the realization of an elemental checked pattern. The periodic variations perpendicular to the growth direction of the branches are caused by the constant rotation of the sample during growth whilst Ga-rich stripes along the growth direction of the branches are understood to be driven by the different nucleation energies and polarities on facets of different crystal phase at the interface between the catalyst droplets and the branched NW tip. These results lead to further comprehension of phase segregation and could assist in the compositional engineering in ternary NWs via harnessing this interesting phenomenon.